Journalistic industries in the internet era: the case of colombian news media outlets in Google News Colombia - Cobos , Tania Lucía (2020)
DOI: 10.26439/contratexto2020.n033.4785 In the era of news media outlets on the internet, the way in which the Colombian news outlets appear in the edition of Google News Colombia in the aspects of identification, visibility and role of provider was analyzed. Google News, owned by Google, is a news aggregator with 72 international editions that, in an automated way, without human editors, takes snippets of news from thousands of news media outlets, without paying for it, and organizes, hierarchises and offers them to audiences through web and apps. After a web scraping carried out between January 1 and March 31, 2015, 1 222 320 news were captured, from which 1216 news media were identified, where 111 were Colombians, who in turn contributed 63 % of the captured news and 42,3 % of the unique news presented in this edition. ElTiempo.com and Caracol Radio, large, traditional and popular news media outlets, were identified as those with the highestaggregate shares, both in captured news (visibility) and in unique news (provider). In parallel, from a documentary review, it was found that ElTiempo.com applied a policy of not mentioning Google as a form of protest against the aggregation; as opposed to a small and native digital medium like TuSemanario.com that celebrated it since it appeared alongside large Colombian news media.